Protein Profiling of Thiobacillus ferrooxidans and Pseudomonas fluorescens Mutants during Metal Extraction - Shaikh, S. M.; Shaikh, R. U.; Ade, A. B. (Journal of Scientific Research, 2018)
Proteins are specific for the specific task associated with the cell. The metal extracting bacteria, Thiobacillus ferrooxidans and Pseudomonas fluorescens have two different mechanisms for the metal extraction. One extracts the metals by donating electrons and by doing self-oxidation and another is accumulating the metals onto its cell surface which is negatively charged. Therefore to differentiate the task of metal extraction protein profiling was done and compared. The water soluble proteins were analyzed through SDS-PAGE. There was no significant difference in the profiles of both.